Growth over the very long-run: Implications of a specific factors model of economic development with endogenous technological change - Volker Caspari; Sabine Eschenhof-Kammer; Klaus Pertz (Technische Universität Darmstadt, Department of Law and Economics, 2012)
We use the two-sector specific factors model, which is known from the theory of international trade, in a growth context to describe major trends of long-run economic development. The endogenous technical progress functions establish the link between the agricultural and the manufacturing sector through the ratio of agricultural to total employment, which is determined by the savings propensities of wage-earners, landlords and capitalists, and by the investment ratio in manufacturing. Without reference to more complicated micro-based models of human capital accumulation highlighting changes in preferences of households and/ or shifts in attitudes of firms towards education, the calibrated two-sector specific factors model can replicate major historical trends and structural turnarounds.
Keywords: E13; N1; O41; 330; economic growth; technical change; distribution of income; Industrial Revolution